The Role of Community-Based Men’s Sheds in Health Promotion for Older Men: A Mixed-Methods Systematic Review - Linda Foettinger; Birte Marie Albrecht; Thomas Altgeld; Dirk Gansefort; Carina Recke; Imke Stalling; Karin Bammann (American Journal of Men's Health, 2022)
Men’s Sheds are a community-based health promotion concept which brings men together to engage in joint activities. Prior research reported beneficial effects on health and well-being of the participants; however, evidence is limited. The main objective of this systematic review is to provide an extensive overview of current research on the effectiveness of Men’s Sheds on self-rated health, social isolation, and well-being by applying a mixed-methods approach. In addition, this review aims to identify how to successfully transfer and implement the concept. Eligible for inclusion were all studies published in English, German, or French that specifically referred to the concept of Men’s Sheds. Four databases were searched for eligible studies, followed by a hand search on websites and reference lists. Methodological quality of included studies was assessed using checklists developed by the Joanna Briggs Institute. Following the convergent integrated approach, quantitative data were transformed and merged with qualitative data to conduct a thematic analysis. Overall, 35 qualitative, nine quantitative, and eight mixed-methods studies were included. We found evidence regarding benefits of shed participation on self-rated health, social isolation, and well-being. We identified three key characteristics of a successful Men’s Shed, including appropriate shed facilities, sufficient funding as well as a participant-driven management and organization of the shed. This mixed-methods systematic review provides a comprehensive overview of the evidence base concerning Men’s Sheds and highlights the need for longitudinal studies investigating causal relationships and gathering sufficient information on how to successfully transfer and implement the concept of Men’s Sheds in other countries.